Theoretical aspects of hydrolysis of peptide bonds by zinc metalloenzymes - Navrátil, Václav; Klusák, Vojtěch; Rulíšek, Lubomír (Chemistry (Weinheim an der Bergstrasse, Germany), 2013)
Activation and reaction energies for four model systems capturing the essential physicochemical features of the hydrolysis of the peptide bond have been calculated at various level of theory, including the presumably accurate CCSD(T) calculations. The models studied covered a part of the spectrum encountered in biological systems: the hydrolysis in the absence of metal ions (represented by formamide and Ala-Ala) and the hydrolysis in the presence of one and two zinc(II) ions, mimicking the active sites of mono- and dizinc metallopeptidases, respectively (by using thermolysin and glutamate carboxypeptidase II as the model catalytic systems and formamide as the model substrate). The results obtained using CCSD(T)/def2-TZVP and CCSD(T)/aug-cc-pVTZ calculations were used as the benchmark values to which the set of cheaper methods, such as (RI-)DFT, (RI-)MP2, and SCS-MP2, were referenced. It was shown that deviations of 3-5 kcal mol(-1) (translating to 2-3 orders in reaction constants) with respect to the reference CCSD(T) barriers are frequently encountered for many correlated methods and most of studied DFT functionals. It has been concluded that from the set of wave-function methods, both MP2 and SCS-MP2 methods can be recommended for smaller models (measured by the mean absolute deviation of the activation barriers over the four systems studied), whereas among the popular DFT functionals, B3LYP and especially M06-2X are likely to be reasonable choices for calculating the activation barriers of zinc metallopeptidases. Finally, with the model of glutamate carboxypeptidase II, issues related to the convergence of the calculated barriers with the size of the model system used as the representative of the enzyme active site were addressed. The intricacies related to system truncation are demonstrated, and suggest that the correlated wave-function methods may suffer from problems, such as intramolecular BSSE, which make their usage for the larger system questionable. Altogether, the presented data should contribute to efforts to understand enzymatic catalysis more deeply and to gain control of the accuracy and deficiencies of the available theoretical methods and computational approaches.
Keywords: Animals; ab initio calculations; transition states; metaloproteiny; hydrolýza; Quantum Theory; dipeptidy; Zinc; Dipeptides; peptides; Models, Molecular; proteasy; zinek; Peptide Hydrolases; molekulární modely; katalytická doména; Hydrolysis; Thermodynamics; Metalloproteins; metalloenzymes; hydrolysis; Formamides; zvířata; formamidy; kvantová teorie; termodynamika; Catalytic Domain